High‐Entropy Photothermal Materials - He, Cheng‐Yu; Li, Yang; Zhou, Zhuo‐Hao; Liu, Bao‐Hua; Gao, Xiang‐Hu (Advanced materials (Weinheim), 2024)
High‐entropy (HE) materials, celebrated for their extraordinary chemical and physical properties, have garnered increasing attention for their broad applications across diverse disciplines. The expansive compositional range of these materials allows for nuanced tuning of their properties and innovative structural designs. Recent advances have been centered on their versatile photothermal conversion capabilities, effective across the full solar spectrum (300–2500 nm). The HE effect, coupled with hysteresis diffusion, imparts these materials with desirable thermal and chemical stability. These attributes position HE materials as a revolutionary alternative to traditional photothermal materials, signifying a transformative shift in photothermal technology. This review delivers a comprehensive summary of the current state of knowledge regarding HE photothermal materials, emphasizing the intricate relationship between their compositions, structures, light‐absorbing mechanisms, and optical properties. Furthermore, the review outlines the notable advances in HE photothermal materials, emphasizing their contributions to areas, such as solar water evaporation, personal thermal management, solar thermoelectric generation, catalysis, and biomedical applications. The review culminates in presenting a roadmap that outlines prospective directions for future research in this burgeoning field, and also outlines fruitful ways to develop advanced HE photothermal materials and to expand their promising applications. This review delves into high‐entropy photothermal materials, highlighting their advantages, recent progress, and wide‐ranging applications in energy, environment, and healthcare. Structured to deepen understanding from basic principles to advanced uses, it sheds light on research trends, challenges, and future directions, making it a key resource for researchers across various scientific disciplines.